Penanaman Nilai-Nilai Profil Pelajar Pancasila melalui Pembelajaran Pendidikan Kewarganegaraan di SD N Kalukuan IV Kota Makassar - Rizal, A.; Misbahuddin, Misbahuddin; Burhan, Burhan; Arsyad, Susalti Nur; Irwandi, Andi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this research was conducted to describe one of the innovations in Civics learning through the subject matter of Archipelagic Insights which can instill the values of the Pancasila Student Profile in students. As the goal of Civics learning is to educate citizens to become good citizens, which can be described as citizens who are patriotic, tolerant, loyal to the nation and state, religious, changeable, and true Pancasila. Data collection techniques using the approach of observation, interviews, and documentation. This study uses a type of qualitative research. Data reduction was carried out and then analyzed using triangulation sources. The results of this study indicate that: Citizenship Education Learning through archipelago insight material at SDN Kalukuan IV Makassar City provides broader knowledge and insights to students about Indonesia's diversity, so that students can get to know the regions in Indonesia, their customs, culture, and natural wealth is expected to grow the love of the nation and state. By using the Discovery Learning method and interesting learning packaging through animations and interactive videos (educational games) so that students do not feel heavy with the learning load. Keywords: Citizenship Education, Learners, Pancasila Student Profile